Marxist state governments in India - "Nossiter, T.J." (London, 1988)
This volume in the series relates only to those states in India which profess to be Marxist regimes - chiefly Kerala and West Bengal, though the small state of Tripura is also discussed. There is a sketch of India as a whole, followed by a resume of the history of communism in India in order to show how these states relate to the country and movement of which they are a part. Thereafter the states are discussed in succession with respect to their political traditions, social structures, political and economic systems, centre-state relations and state government policies. Whatever happens in India at national level, the experiment which began in 1957 is likely to continue in Kerala, West Bengal and Tripura. It is an experiment which is important not only to the more than 80 million people directly affected, but to anyone seeking to understand the diversification of communism.
Keywords: Communism India History